Relevansi Prinsip Pesantren Sami’na wa Atho’na dalam Filsafat Etika Immanuel Kant - Iklila, Difla; Fauzi, Ahmad (JURNAL AL-AQIDAH, 2024)
This study examines the values embedded in the pesantren education system that form a patron-client relationship between kiai and santri. This relationship is characterized by the characteristics of imbalance, individuality, and breadth, which are reflected in pesantren educational literature such as Kitab Ta'lim Muta'allim. Qualitative methods will be used in writing this article, with qualitative methods integrating field research and literature studies to explore the relevance between the pesantren ethical principle of sami'na wa atho'na which means "we hear and we obey" with Immanuel Kant's ethical philosophy, particularly the ethical theory of obligation or deontology. Kant, who lived in the 18th century, developed an ethical concept centered on the categorical imperative and the importance of good will and the autonomy of the will, which emphasized universal moral obligation and the attainment of eternal happiness. This article highlights how the principle of sami'na wa atho'na is still relevant and respected in the context of pesantren, despite differences with modern educational approaches that encourage students to be more active and critical. This research provides insight into how traditional pesantren values survive and interact with modern ethical concepts, as well as their implications for the dynamics of education and morality in Indonesia.